2022
DOI: 10.3390/pathogens12010009
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Genomic Characterization of Escherichia albertii in Migratory Birds from Poyang Lake, China

Abstract: Escherichia albertii is an emerging zoonotic foodborne enteropathogen leading to human gastroenteritis outbreaks. Although E. albertii has been isolated from birds which have been considered as the potential reservoirs of this bacterium, its prevalence in migratory birds has rarely been described. In this study, E. albertii in migratory birds from Poyang Lake was investigated and characterized using whole genome sequencing. Eighty-one fecal samples from nine species of migratory birds were collected and 24/81 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In previous surveillance, E. albertii was typically found in poultry feces/intestinal contents and poultry meat, wild birds, and raccoons [ 7 , 12 , 18 , 19 ]. People might be infected through contact with these animals or by consuming contaminated water, vegetables, and meat [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous surveillance, E. albertii was typically found in poultry feces/intestinal contents and poultry meat, wild birds, and raccoons [ 7 , 12 , 18 , 19 ]. People might be infected through contact with these animals or by consuming contaminated water, vegetables, and meat [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Later, matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF/MS, Bruker Daltonics, Germany) was performed in clinical laboratory, which displayed presumptive identification of E. albertii (score 2.44). Subsequently, the isolate was transferred to Zigong Center for Disease Control and Prevention, and was confirmed as E. albertii by the diagnostic triplex-PCR targeting clpX , lysP , and mdh genes, as previously described [ 12 ]. Then, the antimicrobial susceptibility was evaluated using VITEK2 Compact (bioMérieux, Lyon, France) and strain ESA303 was sensitive to all antibiotics, including ampicillin, amikacin, aztreonam, ciprofloxacin, cefotetan, ertapenem, cefepime, gentamicin, levofloxacin, cotrimoxazole, tobramycin, piperacillin/tazobactam, ampicillin/sulbactam, ceftriaxone, imipenem, ceftazidime, amoxicillin/clavulanate, cefuroxime, cefzolin, meropenem, and cefoperazone/sulbactam.…”
Section: Identificationmentioning
confidence: 99%
“…A total of 205 whole genome sequenced E. albertii strains from China were used in this study, including 201 strains previously reported [6,12], one newly sequenced strain ESA302 in this study, and three collected from the NCBI database (https://www.ncbi.nlm. nih.gov/datasets/, accessed on 9 October 2022).…”
Section: Isolates Collectionmentioning
confidence: 99%
“…In 2004, large-scale mortality of finch species (Carduelis flammea) occurred in Alaska, and E. albertii was identified as the probable etiology [10]. In recent years, E. albertii strains have been identified widely in avian, mammal species, raw meats, and humans [11][12][13][14]. However, the close association of animal or food vehicles with human infections remains unclear.…”
Section: Introductionmentioning
confidence: 99%